Racy Sexy - Sorting through the Traffic Jam at the Intersection of Race, Culture, Ethnicity and Sexuality: A Model for Intergenerational Multicultural Sexuality Education for Parents - Cynthia Low (Adult Education Research Conference, 2002)
This paper looks at developing a multicultural model for sexuality education that focuses on parents as the advocates for increased understanding and support for healthy sexual behaviors among youth.